3M microfoam™ surgical tape prevents nasal pressure injury associated with nasotracheal intubation: A randomized double-blind trial. Issue 2 (13th January 2023) - Hashimoto, Mayumi; Sato (Boku), Aiji; Sento, Yoshiki; Kamimura, Yuji; Kako, Eisuke; Okuda, Masahiro; Tachi, Naoko; Okumura, Yoko; Kuroda, Izumi; Hoshijima, Hiroshi; Ito, Hidekazu; Sobue, Kazuya
Abstract : Background: 3M microfoam™ surgical tape (3ST: 3M Japan Limited) is used for pressure wound control of medical equipment. It is cushioned and can be fitted to any body part. Here we investigated whether 3ST prevents nasal pressure injury associated with nasotracheal intubation (NTI). Methods: We conducted a prospective, randomized double-blind study, enrolling 63 patients aged 20 to 70 years, who underwent general anesthesia with NTI. They were divided into 2 groups; those treated with 3ST (group S ; n = 31) and control (group C ; n = 31). After NTI and before securing the nasotracheal tube, a 35 × 25 mm 3ST was used to protect the nasal wing in group S, and the nasotracheal tube was fixed in place after NTI without protection in group C . The primary outcome was the presence or absence of nasal pressure injury after extubation. The Chi-Square test was used to assess the association between the 2 categorical variables. Results: Nasal pressure injury was observed in 7 and 19 patients from groups S and C, respectively, representing a significant difference between the 2 groups (24.1% vs 67.8%, P = .001). Remarkably, none of the patients developed ulcers. Conclusion: 3ST prevents nasal pressure injury associated with NTI.